(untitled) (Colloquia Comparativa Litterarum, 2025)
Rendering national, cultural and historical references into the target language is one of the major challenges in translating folklore narratives. The paper examines the approaches to Norwegian realia (i.e. words for culture-specific items) denoting currency units (daler, skilling and mark), adopted by the Bulgarian translators of the Norwegian Folktales collected by Peter Christen Asbjørnsen and Jørgen Moe. The translation strategies are discussed against the backdrop of the major role of the Folktales in fostering Norwegian national identity during the National Romanticism period. The paper provides some theoretical considerations relating to the multitude of factors which underlie the possible translation strategies, e.g. the genre specifics of the source text, the target group of the translation, the degree of the national overtones’ intensity and the nature of the realia’s denotata.